Risk and protective factors for suicide: a populational case-control study, Brazil, 2019 - Ruiz, Ana Maria Pita; Fernandez, Mirla Randy Bravo; Komoda, Denis Satoshi; Treichel, Carlos Alberto dos Santos; Cordeiro, Ricardo Carlos (Revista de Saúde Pública, 2023)
OBJETIVE: To estimate risk and protection factors associated with suicide in Campinas, Brazil, in 2019. METHODS: This is a populational case-control study analyzing 83 cases of suicide that occurred in 2019 in Campinas, a Brazilian city with about 1.2 million inhabitants. Controls were composed of 716 inhabitants. An adjusted multiple logistic regression was used. Cases and controls were the dichotomous response variables. Sociodemographic and behavioral variables were the predictor variables. RESULTS: The categories which presented higher risk of suicide were: males [OR = 5.26 (p < 0.001)]; people aged 10–29 years [OR = 5.88 (p = 0.002)]; individuals without paid work [OR = 3.06 (p = 0.013)]; individuals presenting problematic use of alcohol [OR = 33.12 (p < 0.001)] and cocaine [14.59 (p < 0.007)]; and people with disabilities [OR = 3.72 (p < 0.001]. Moreover, the perception of fear was associated with reduced suicide risk [OR = 0.19 (p = 0.015)]. Higher district HDI levels also showed a 4% decrease in risk for each 0.01 increase in district HDI levels [OR = 0.02 (p = 0.008)]. CONCLUSIONS: This study evidenced the association between sociodemographic and behavioral variables and suicide. It also emphasized the complexity in the dynamics between personal, social, and economic factors to this external cause of death.